2011
DOI: 10.1016/j.pain.2010.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Dural afferents express acid-sensing ion channels: A role for decreased meningeal pH in migraine headache

Abstract: Migraine headache is one of the most common neurological disorders. The pathological conditions that directly initiate afferent pain signaling are poorly understood. In trigeminal neurons retrogradely labeled from the cranial meninges, we have recorded pH-evoked currents using whole-cell patch-clamp electrophysiology. Approximately 80% of dural afferent neurons responded to a pH 6.0 application with a rapidly activating and rapidly desensitizing ASIC-like current that often exceeded 20 nA in amplitude. Inward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
123
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 32 publications
18
123
0
1
Order By: Relevance
“…Functional changes of several types of ion channels may contribute to an altered state of neuronal 6 excitability of trigeminal afferent neurons innervating the dura (Yan and Dussor, 2014). The majority of rat dural afferents display ASIC currents, which are likely mediated by ASIC3-containing channels (Yan et al, 2011). Application of pH 5 synthetic interstitial fluid to the dura of rats induced facial and hind paw allodynia.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
See 1 more Smart Citation
“…Functional changes of several types of ion channels may contribute to an altered state of neuronal 6 excitability of trigeminal afferent neurons innervating the dura (Yan and Dussor, 2014). The majority of rat dural afferents display ASIC currents, which are likely mediated by ASIC3-containing channels (Yan et al, 2011). Application of pH 5 synthetic interstitial fluid to the dura of rats induced facial and hind paw allodynia.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…Application of pH 5 synthetic interstitial fluid to the dura of rats induced facial and hind paw allodynia. Facial allodynia is often associated with migraine (Yan et al, 2011). Amiloride has been reported to inhibit cortical spreading depression in rodents, and improved aura and headache severity in 4 of 7 patients of a small clinical trial (Holland et al, 2012).…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…The SIF consisted of 10 mM HEPES, 5 mM KCl, 1 mM MgCl 2 , 2.5 mM CaCl 2 , and 135 mM NaCl (adjusted to pH 7.4). The IS contained 1 mM histamine, serotonin, and bradykinin and 0.1 mM prostaglandin E 2 in pH 7.4 SIF [5, 6]. Sham mice were habituated to the test room and recording cage with the same protocol as the mice in other groups but were not subjected to drug administration.…”
Section: Methodsmentioning
confidence: 99%
“…However, the composition of IS is complex, as it contains unstable, small peptides that are difficult to store. Yan et al have previously reported a study on acute pH-evoked migraine-related pain behaviour, such as facial and hind paw allodynia [5]. An animal model with repeated activation of the dural nociceptors is needed to identify both new mechanisms of trigeminal pain and important factors involved in the transition from episodic to chronic trigeminal pain.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The rats were deeply anesthetized with 10% chloral hydrate (4 mL/kg) and placed in a stereotaxic apparatus (RWD 68030; RWD Life Science Co., Ltd., Shenzhen, China). The rats were topically anesthetized with 2% lidocaine (0.5 mL), applied to the skin.…”
Section: Fast Dil Retrograde Labeling Of Tg Neurons Innervating the Dacfmentioning
confidence: 99%